A nitrogen-doped ordered mesoporous carbon/graphene framework as bifunctional electrocatalyst for oxygen reduction and evolution reactions. (December 2016) - Zhang, Changlin; Wang, Biwei; Shen, Xiaochen; Liu, Jiawei; Kong, Xiangkai; Chuang, Steven S.C.; Yang, Dong; Dong, Angang; Peng, Zhenmeng
Abstract: Highly ordered N-doped mesoporous carbon/graphene frameworks (N-MCF/N-MGF) were prepared using superlattice of self-assembled Fe3 O4 nanoparticles as template. The prepared N-MCF catalyst shows enhanced oxygen reduction reaction (ORR) activity compared with commercial Pt/C catalyst. The N-MGF catalyst demonstrates lower oxygen evolution reaction (OER) overpotential (324 mV at 10 mA cm −2 ) than most of the previously reported carbon based materials, non-noble metal oxides and their hybrids, and comparable with noble metal oxides (ruthenium/iridium oxide, RuO2 and IrO2 ) catalysts. The prepared N-MGF catalysts also exhibit negligible mass transfer resistance, good durability and bifunctionality in ORR and OER. The significantly improved electrocatalytic performance results from their large surface area, ordered pores, excellent internal diffusion property, and superior intrinsic conductivity. The materials show great potential for various applications in energy conversion and storage, including fuel cells, electrolyzers and metal-air batteries. Graphical abstract: Highlights: N-doped mesoporous carbon/graphene framework (N-MCF/MGF) with ordered pores was prepared. The N-MCF/MGF outperforms Pt/C in ORR and RuO2 /C in OER showing high activity and good durability. The negligible mass transfer resistance of the N-MCF/MGF in ORR benefits from their highly ordered structure. The highly ordered N-MCF/MGF can be potentially implemented in fuel cells, electrolyzers and metal-air batteries.